Nutrition-sensitive policy pathways for dealing with climate extremes in Zambia - Jennings, Stewart; Chomba, Christian (International Center for Tropical Agriculture, 2024)
Warming and extreme drought are projected to become more severe by 2050. To cope with climate change, a suite of domestic nutrient-rich crops, coupled with early warning systems and a resilient trade network are key to avoiding increased reliance on food aid and higher risk of famine. Policies need to consider agriculture, nutrition, trade and climate factors simultaneously. Progress can be made by incorporating nutritional requirements into food supply measures, both through agricultural expansion targets and through developing a robust trade network that can source vital commodities – not just staple crops but the vegetables and fruits that can improve nutrition security, so not only calories but wider nutritional needs are met in future.